BACTERIAL ISOLATES ASSOCIATED WITH PELVIC INFLAMMATORY DISEASE AMONG FEMALE PATIENTS ATTENDING SOME HOSPITALS IN ABUJA, NIGERIA. - Spencer, T H I; Umeh, P O; Irokanulo, E; Baba, M M; Spencer, B B; Umar, A I; Ardzard, S A; Oderinde, S; Onoja, O (African Journal of Infectious Diseases (AJID), 2013)
Background: Pelvic inflammatory disease refers to any infection in the female lower reproductive tract that spreads to the upper reproductive tract. The disease comprises a spectrum of inflammatory disorders of the upper female genital tract, including any combination of endometritis, salpingitis, tubo-ovarian abscess and pelvic peritonitis. PID is not a notifiable disease in most countries, so accurate statistics are not available. This situation is not in any way different here in Nigeria and more so in the Federal Capital Territory, Abuja where this research was conducted, there had never been any published report so far on PID. It therefore became pertinent that such studies be carried out to evaluate the bacterial organisms which may be associated with the disease in this part of Nigeria so that health care providers could take a better look at this affliction in women.Materials and Methods: Endocervical swabs totalling 100 were aseptically collected from patients with confirmed Pelvic Inflammatory Disease (PID), attending some hospitals in Abuja, Nigeria for detection of bacterial pathogens based on cultural and biochemical characterisation tests. Antibiogram was also conducted on the identified bacterial isolates.Results: Out of the 100 samples analysed, 43% yielded pure cultures of bacterial isolates, 2% yielded mixed cultures while no bacterial growths were recorded from the remaining 55% samples. Organisms encountered were Staphylococcus aureus (16%), Escherichia coli (10%), Streptococcus faecalis (8%), Pseudomonas aeruginosa (4%), Streptococcus pyogenes (3%), Klebsiella pneumoniae (3%), Proteus rettgeri (2%) and Proteus mirabilis (1%). The highest percentage occurrence of pathogenic isolates was observed in polygamous married patients (90%). The age group most affected falls within the mean age 30.5 years (68%) while the least affected group falls within the mean age 40.5 years (5%). There was a significant difference in the acquisition of PID in relation to marital status (P < 0.05). However there was no significant difference in the acquisition of the disease with respect to age (P > 0.05). Antibiogram patterns of pathogenic isolates revealed varied resistance to most of the antibiotics employed. Cefotaxime (a new generation cephalosporin antibiotic) was established in this study as the best antimicrobial agent for treatment of PID due to Gram-positive and Gram-negative bacteria isolated from the women examined.Conclusion: In conclusion, Pelvic inflammatory disease is a major health problem in developed or developing countries of the world. PID is not a notifiable disease, as accurate statistics on disease prevalence are rarely available. There is therefore no doubt thousands of young women have salpingitis every year and their sheer number makes it an important health problem. PID hence can be said to be a very serious complication of sexually transmitted disease which should be critically and promptly handled by healthcare providers. The right type sample should be aseptically collected and be appropriately handled for laboratory investigation. Treatment of PID should be initiated as soon as the presumptive diagnosis has been made. Immediate administration of antibiotics has been effective in the long-term sequelae associated with PID, especially new generation antibiotics, such as cefotaxime as recorded in this study.